MARKETING PERFORMANCE ASSESSMENT BASED ON A SYSTEMIC ANALYSIS OF CONSUMER BUYING BEHAVIOR - Жук, Оксана (SWorldJournal, 2025)
The article explores the issue of limited use of psychological models in marketing practice and the consequences of such an approach for accurately predicting consumer behavior. The author proposes a classification of four key personality models – behavio